Exploring Strategies for Attenuating Changes in Bone Mineral Density in MSM on TDF/FTC HIV Pre-exposure Prophylaxis. (4th October 2017) - Kortenaar, Jean-Luc; Cheung, Angela; Mewa, Shabbir; Waugh, Esther; Rubin, Laurence; Tan, Darrell
Abstract: Background: Daily oral tenofovir disoproxil fumarate/emtricitabine (TDF/FTC, Truvada ® ) used as HIV pre-exposure prophylaxis (PrEP) decreases HIV incidence but decreases bone mineral density (BMD) as well. We sought to determine whether vitamin D supplementation, higher dietary calcium intake, and bone loading exercise can attenuate decreases in BMD during the first 12 months of daily TDF/FTC PrEP use. Methods: Participants were adult men who have sex with men from the PREPARATORY-5 pilot study who had dual-energy X-ray absorptiometry (DXA) scans at both baseline and 12 months ( n = 39). Self-reported vitamin D supplementation was collected prospectively, whereas data on diet and exercise was obtained retrospectively, using validated questionnaires administered after the study period. Wilcoxon Mann–Whitney tests were used to determine the association between median percent changes in bone mineral density (BMD) and (1) those with and without vitamin D supplementation, (2) those with adequate (1, 000 mg/day) and deficient (<500 mg/day) dietary calcium intake, and (3) those in the highest tertile vs. lowest tertile of contemporaneous bone loading exercise. The associations between these variables and the trabecular bone score (TBS) were also explored. Results: Median (interquartile range) participant age was 34 (29, 39) years, 74% were white and most had some post-secondary education. Compared with those not using vitamin D, those taking any vitamin D supplementation had a smaller median percent decline in the lumbar spine's trabecular bone score (−1.42% vs. -3.99%, P = 0.06), no difference in the BMD of the lumbar spine (−2.11% vs. to 2.14%, P = 0.38), but greater declines in the median BMD at the femoral neck (−1.75% vs. −1.17%, P = 0.32) and total hip (−0.89% vs. −0.69%, P = 0.27). There were no significant differences in BMD or TBS between those with high and low dietary calcium intake, or between those in the highest and lowest tertiles of bone loading exercise. Conclusion: There is some suggestion that vitamin D supplementation might have an attenuating effect on the TBS of the lumbar spine. The relationships between vitamin D supplementation, calcium dietary intake and bone loading exercise with changes in BMD due to TDF/FTC PrEP requires further investigation. Disclosures: All authors: No reported disclosures.